High-flow nasal cannula therapy for initial oxygen administration in acute hypercapnic respiratory failure: study protocol of randomised controlled unblinded trial. Issue 1 (8th January 2021) - Alnajada, Asem; Blackwood, Bronagh; Mobrad, Abdulmajeed; Akhtar, Adeel; Shyamsundar, Murali
Abstract : Introduction: Acute respiratory failure is a common clinical condition accounting for nearly 116 000 admissions in the UK hospitals. Acute type 2 respiratory failure is also called acute hypercapnic respiratory failure (AHRF) and characterised by an elevated arterial CO2 level of >6 kPa due to pump failure. Acute exacerbation of chronic obstructive pulmonary disease is the most common cause of AHRF. High-flow nasal therapy (HFNT) is a new oxygen delivery system that uses an oxygen-air blender to deliver flow rates of up to 60 L/min. The gas is delivered humidified and heated to the patient via wide-bore nasal cannula. Methods and analysis: We hypothesised that HFNC as the initial oxygen administration method will reduce the number of patients with AHRF requiring non-invasive ventilation in patients at 6 hours post intervention when compared with low-flow nasal oxygen (LFO). A randomised single-centre unblinded controlled trial is designed to test our hypothesis. The trial will compare two oxygen administration methods, HFNT versus LFO. Patients will be randomised to one of the two arms if they fulfil the eligibility criteria. The sample size is 82 adult patients (41 HFNT and 41 LFO) presenting to the emergency department. Ethics and dissemination: Ethical approval was obtained from the Office for Research Ethics Committees Northern Ireland (REC reference: 20/NI/0049). Dissemination will be achieved in several ways: (1) the findings will be presented at national and international meetings with open-access abstracts online and (2) in accordance with the open-access policies proposed by the leading research funding bodies we aim to publish the findings in high-quality peer-reviewed open-access journals. Trial registration number: The trial was prospectively registered at the clinicaltrials.gov registry (NCT04640948 ) on 20 November 2020.